PREVALENSI DERMATITIS KONTAK PADA PASIEN USIA LANJUT DI POLIKLINIK KULIT DAN KELAMIN RSUP Dr.SARDJITO YOGYAKARTA - , LANNY IRIANTI KUSWADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Contact dermatitis is an inflammatory reaction that is accompanied by the presence of intercellular edema in the epidermis as the skin interacts with a particular exposure. The number of elderly people in Yogyakarta has increased each year. This is evidenced by data from the BPS in 2010 the number of elderly population of 454.200 people (13.2%) of the total population. In old age will decrease the function of the skin. The existence of subtle changes that can affect the comfort and function of the skin as a structure that is easily visible and affects an impression. Change the look and function of normal skin caused by aging is called intrinsic aging. Purpose: To determine the prevalence of contact dermatitis in elderly patients and materials are suspected as the cause. Methods: This is a descriptive study with cross sectional approach. Patients with age â¥ 60 years who were diagnosed as Irritant Contact Dermatitis and Allergic Contact Dermatitis at the Dermatology Polyclinic Dr.Sardjito Hospital in Yogyakarta. Results: The results of the data collection period 1 January 2010- 31 December 2010 registers in 93 elderly patients found that the incidence of Irritant Contact Dermatitis consisting of 24 cases (25.8%) and the incidence of Allergic Contact Dermatitis consisting of 69 cases (74.2%) , while the material is suspected as the cause of Irritant Contact Dermatitis and Allergic Contact Dermatitis are 17 types and the most common cause contact dermatitis in elderly patients comprised 20.4% of the cause is still unknown, 16.1% for hair polish, 12.9 % for plants and 6.5% because footwear. Conclusion: 93 elderly patients on register data period 1 January 2010-31 December 2010 that the highest prevalence occurs in Allergic Contact Dermatitis is 69 persons (74.2%). Material suspected as the cause of contact dermatitis is the most overall unknown cause (20.4%), hair polish (16.1%), herbs (12.9%) and footwear (6.5%). At least a lot of Irritant Contact Dermatitis are unknown (8 cases), while the most widely Allergic Contact Dermatitis caused by hair polish (15 cases)